Body, Morality, and Gender Surveillance in the Netflix Series Lady’s Companion and the Film Gowok: Kamasutra Jawa - Nailul Ulah Al Chumairoh Machfud; Philosa Kasyutiantara Denpabhara (Journal of Innovative and Creativity, 2026)
This study aims to reveal how the female body is constructed, moralized, and surveilled through the figure of the chaperone in Western culture and the gowok in Javanese tradition. Employing a comparative literature approach and a qualitative descriptive method, this research analyzes two cultural texts: the Netflix series Lady’s Companion (2025) and the film Gowok: Kamasutra Jawa (2025). The theoretical framework draws on Michel Foucault’s concept of the politics of the body, Judith Butler’s theory of gender performativity, and Gayatri Spivak’s notion of subalternity. The findings indicate that in Western society the female body is repressed through public morality and norms of decorum, while in Javanese culture it is exploited through patriarchal spirituality that positions women as instruments of masculine knowledge and initiation. In Lady’s Companion, the character Elena Bianda functions as a moral agent who supervises the conduct and bodily comportment of young noblewomen to preserve family reputation. In contrast, Gowok: Kamasutra Jawa presents Nyai Gowok as a spiritual teacher whose body becomes a symbolic site of knowledge and discipline, yet remains embedded within the patriarchal logic of Javanese court culture. Both figures demonstrate distinct yet interconnected mechanisms of gender surveillance, rooted in the same patriarchal logic that controls the female body through moral and spiritual institutions. By juxtaposing these two cultural frameworks, this study contributes to cross-cultural discourse on gender, morality, and embodiment, showing how literature and film reflect and reproduce the politics of the female body.